The Influence Of Construction Value, Number Of Construction Companies And Import Value On VAT And STLGs Revenue - Prawira, Zain Yudha; Irawan, Ferry (Educoretax, 2024)
This study examines the influence of construction value, number of construction companies and import value on VAT and STLGs revenues in Indonesia. The data used is time series data downloaded from the Central Statistics Agency and the Ministry of Public Works and Public Housing which covers all regions throughout Indonesia for the period 2007 to 2022. This research uses a multiple linear regression test with the OLS (ordinary least square) method so that it can explain the influence of construction value, number of construction companies and import value on VAT and STLGs revenues in Indonesia. The independent variables used are construction value, number of construction companies and import value, while the dependent variable is VAT and STLGs revenues. The research results show that the construction value and import value each have a positive and significant effect on VAT and STLGs revenues partially, while the number of construction companies has a negative but not partially significant effect. Simultaneously, the construction value, number of construction companies and import value have a significant effect on VAT and STLGs revenues in Indonesia. This research can be a reference, especially for the Directorate General of Taxes in developing strategies to explore the potential to increase VAT and STLGs revenues in Indonesia through construction and import activities.